Influence of blade installation angle spanwise distribution on the energy characteristics of mining contra-rotating axial flow fan - Yongping Chen; Ronghua Liu; Chunyu Liu; Shiqiang Chen; Shixian Wu; Dong Liu; Yangyi Li; Xuan Zhou (Scientific Reports, 2025)
Abstract As the global demand for energy conservation increases, achieving efficient energy conversion in fans has become a significant challenge in the field of mine ventilation. To investigate the influence of the blade installation angle distribution in the spanwise direction on the energy characteristics of mining counter-rotating axial flow fan, three blade optimization schemes were proposed in this paper. The internal flow field of the fan was obtained by numerical simulation and experimental methods. Based on the entropy production theory, the correlation between energy loss and flow field parameters was established, thus achieving the quantitative assessment of energy loss. The research findings indicate significant differences in energy characteristics before and after blade optimization, with scheme OP1 (when the optimization case 1 is applied to both the front impeller and rear impeller) demonstrating superior performance. Compared to the original fan, scheme OP1 efficiency and total pressure increase by 1.1% and 1.3%, respectively, under 1.0 Q BEP condition (Q BEP is flow rate at the best efficiency point). Furthermore, under 1.2 Q BEP condition, improvements reach 3.1% and 4.7%, respectively. The improvement in the efficiency of scheme OP1 is mainly attributed to the reduction in the energy loss rate induced by turbulent dissipation within the rear impeller and downstream domain. Notably, distinct differences in the energy loss rates of fan extension pipe for different schemes, the energy loss rate of scheme OP1 is reduced by 24.6% compared to that of the original fan under 1.2 Q BEP condition.